Fusion of horizons: a case study of the pedagogy of transformative hope for Muslim women’s empowerment in Malaysia - Hussien, Suhailah (Indiana University Press, 2022)
The purpose of this chapter is twofold. The first is to examine the pedagogy of hope for the empowerment of Muslim, and second is to explore how engaging in it would assist Muslim in broadening their ‘horizons’, consequently bonding the ties of the Muslim societies. The chapter begins with the attempt to define pedagogy of hope for Muslim that would result in the ‘conscientization’ or raising the consciousness of Muslim from hegemony in their society. The first part of the chapter delineates what hope is and the form of oppression that engulfs Muslims. Then, it identifies the hegemony that underlies the system and social relations in a Muslim society by conceptualizing the idea of social critique. Exploring the dynamics of social and self-critiques, the chapter suggests self-critique through Kazmi’s (2000) notion of understanding the Signs of Allah (in the Qur’an and the world) that can assist Muslim to become active meaning makers through the deconstruction and reconstruction of meanings. The dialectical relationship of self and social critique is further explained through Gadamer’s idea of prejudices and horizons, which to some extent has divided and caused conflict among Muslim societies. The pedagogy of hope described in the first part chapter takes the form of critical pedagogy in the classroom practice in the second part of the chapter. The second part of the chapter presents a case study of Muslim students’ engagement in the pedagogy and its potential in fostering a closer relationship among Muslim of various background and culture. The case study explores the experience of a group of five postgraduate students from different backgrounds, ethnics and culture and their experience of the pedagogy of hope in a master’s course for one semester. The course instructor engaged students in the pedagogy as a process of ‘conscientization’ to counter identified hegemony in their societies, empowering them to bare their views and prejudices, thus developing self and social critiques that set them on the path of changing the world through the deconstruction and reconstruction of meanings. The case study elucidates how the pedagogy of hope was able to broaden students’ views and ‘horizons’ and fused them together despite the differences of their culture and ethnics. In spite of these differences, students also realized that they shared similar forms of oppression, eventually; the pedagogy has helped the students to bond through the self and social critiques that they collectively developed. To conclude, the findings of the case study indicate that the pedagogy of hope grounded in an Islamic worldview can bond Muslim of different ethnics and culture, therefore the pedagogy also has the potential to bond Muslim societies if they engage in the pedagogy at a macro level.